The Effect of Communication, Workload, on Performance with Motivation as an Intervening Variable - Delviana Naveratilova Malau; A Dewantoro Marsono (International Journal of Scientific Multidisciplinary Research, 2023)
The purpose of this study is to determine the Effect of Communication, Workload and Performance with Motivation as an Intervening Variable. This type of research is quantitative research, which is finding scientific proof or testing based on theories and hypotheses. While its nature is the impact of the study, which is looking for influence between one variable and another. This research belongs to a type of comparative causal research that aims to investigate possible causal relationships that exist. The authors chose the sample using saturated sampling techniques because the population size is relatively small. So the number of samples in this study amounted to 150 people. The data collection technique uses a questionnaire with a Likert scale. Data analysis techniques use using the Structural Equation Model (SEM). The results of the study and conclusions in this study are